2004
DOI: 10.1016/j.jpainsymman.2004.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and perceived competence in providing palliative care to terminally ill patients: a survey of primary care physicians

Abstract: We surveyed primary care physicians about their involvement and perceived skills in palliative care. A survey instrument asked how frequently internal medicine and family practice physicians performed 10 palliative care items. Subjects rated their skills in each area. A majority of physicians always or frequently performed all 10 palliative care items, but fewer than 50% of respondents adequately attended to the spiritual needs and economic problems of patients. Interest in palliative care was associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
1
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 21 publications
1
44
1
3
Order By: Relevance
“…This number is very high compared to results from other studies for instance, 89.3% of general practitioners in Wales were reported to have training in pain control, 67.7% in bereavement, and 70.2% in communication (Barclay et al, 2003). On the other hand, survey conducted among physicians in the US, only 36% were found to receive training in palliative care (Farber et al, 2004). One of study conducted in India indicated that physicians lacked of knowledge on palliative care.…”
Section: Discussionmentioning
confidence: 71%
“…This number is very high compared to results from other studies for instance, 89.3% of general practitioners in Wales were reported to have training in pain control, 67.7% in bereavement, and 70.2% in communication (Barclay et al, 2003). On the other hand, survey conducted among physicians in the US, only 36% were found to receive training in palliative care (Farber et al, 2004). One of study conducted in India indicated that physicians lacked of knowledge on palliative care.…”
Section: Discussionmentioning
confidence: 71%
“…This deficit has since been addressed through a national initiative which aims to engage GPs to support aged care facilities to embed the palliative approach guidelines (Palliative Care Australia, 2008). In addition to only caring for a small number of palliative care patients annually (Farber et al, 2004;Mitchell et al, 2005), GPs also have competing educational priorities, making it difficult for GPs who infrequently care for palliative patients to keep up with the expanding knowledge base (Shipman et al, 2001). This preliminary data suggests that increasing Phillips et al / The General Practitioner Perspective 401 GPs' awareness of a palliative approach is important as it may help to address the cure versus palliative care paradox by ensuring that residents' care is grounded in comfort and dignity (Currow & Hegarty, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Although primary care physicians may perform palliative care de facto for some of their patients, many have not received training in palliative care and may not adequately address certain issues such as symptom management, spiritual needs, and economic issues (30,64). A recent study shows that if the primary care physician remains involved, patient and family have less distress (5).…”
Section: Barriers To Further Integration Of Palliative Carementioning
confidence: 99%
“…A recent study shows that if the primary care physician remains involved, patient and family have less distress (5). Educational programs have been successful in teaching physicians, in training and in practice, important knowledge and communication skills used in palliative care (3,6,30,31,80,89), but much more needs to be done to deliver primary palliative care across the health care system. Variation exists with regard to physician willingness to refer patients to a secondary palliative care specialist or team (1,99).…”
Section: Barriers To Further Integration Of Palliative Carementioning
confidence: 99%